Extensive Comparison Results of Coverage Map of Optimum Base Station Location of Digital Terrain with UTD Based Model - Tabakcıoğlu, Mehmet Barış (Electromagnetics Acad, 2020)
In order to provide high quality of service broadcasting systems, predicting the electric field strength in all the receiving points and generating the coverage map of the transmitter are very important. Uniform Theory of Diffraction (UTD) based ray theoretical models could be used to predict the electric field and generate the coverage map in a short time. In order to eliminate the non-successive obstacles in the scenario and to reduce the computation time of UTD Model, Convex Hull (CH) technique is used for the first time. After this point, this model is named as Uniform Theory of Diffraction with Convex hull (UTD-CH) Model. Moreover, how operating frequency, obstacle height, and the distance between the obstacles affect the coverage map of optimum base station location are researched by using UTD based models. In this study, UTD, Slope Uniform Theory of Diffraction (S-UTD), Slope Uniform Theory of Diffraction with Convex Hull (S-UTD-CH), and UTD-CH models are used for comparisons. Furthermore, computation times of UTD based models are compared.
Keywords: [No Keywords]